Four weddings and a sixpence [compact disc, unabridged] : an anthology - Quinn, Julia, 1970-; Sloane, Stefanie; Boyle, Elizabeth; Guhrke, Laura Lee; Quinn, Julia, 1970-; Wells, Mary Jane (Harper Audio, 2016)
Four friends from Mrs. Rochambeaux's Gentle School for Girls who find an old sixpence in their bedchamber and decide that it will be the lucky coin for each of their weddings.